2015
DOI: 10.1016/j.vhri.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Supplier-Induced Demand for Chronic Disease Care in Japan: Multilevel Analysis of the Association between Physician Density and Physician-Patient Encounter Frequency

Abstract: The results of our study indicate the presence of SID in Japan. Further studies should investigate whether more frequent physician-patient encounters provide clinical advantages to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 17 publications
0
33
0
1
Order By: Relevance
“…The results of the present study showed that the majority of participants (65.2%) agreed with the existence of induced demand, which is consistent with previous studies [11][12][13][14][15] . Bogg et al showed that the government's financial support has led to induced demand 7 In Japan, Sekimoto and Ii studied the supply and induced demand for chronic diseases, and reported an increase in induced demand for hypertension and diabetes 24 . The findings of Crivellei et al in Switzerland 25 Delattre and Dormont in France 20 were in line with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study showed that the majority of participants (65.2%) agreed with the existence of induced demand, which is consistent with previous studies [11][12][13][14][15] . Bogg et al showed that the government's financial support has led to induced demand 7 In Japan, Sekimoto and Ii studied the supply and induced demand for chronic diseases, and reported an increase in induced demand for hypertension and diabetes 24 . The findings of Crivellei et al in Switzerland 25 Delattre and Dormont in France 20 were in line with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…18 Although SID has been studied for some time, its existence has not been proved because it is difficult to define the appropriate supply of care. 16 , 21 However, it has been reported that Japan has a higher proportion of gastrectomy among older adults than other countries, 3 , 4 which suggests an oversupply of gastrostomy procedures. Another challenge to detecting SID is that it is difficult to differentiate SID from patient preference.…”
Section: Discussionmentioning
confidence: 99%
“…We used physician density 21 by secondary tier of medical care (STM) as regional factors. STM is the unit of secondary care governed by a prefecture according to Japan's Medical Service Law.…”
Section: Methodsmentioning
confidence: 99%
“…3,5,6 Others suggest that it incents the delivery of unnecessary treatments. [7][8][9] The impact of increased competition on various patient outcomes has been explored in the literature. A systematic review conducted by Léonard et al 10 found that physician density, measured by the physician-to-population ratio, was positively associated with healthcare consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Competition in health care has been studied in relation to different patient outcomes such as increase utilization rates, quality of care and cost. Sekimoto and Li, 8 Van Dijk et al 21 Our study presents the findings of a geospatial analysis, which aims to understand the influence of competition on dentists' clinical decision-making. It is part of a larger study aimed at understanding how different factors-environmental (competition), provider (age, gender, place of initial training, years of experience and perception of debt), practice (age of practice, number of hours worked/week, number of hygienists employed and number of patients seen/day) and patient factors (insurance status)-influence the clinical decision-making of dentists in Ontario, Canada's largest dental care market.…”
Section: Introductionmentioning
confidence: 99%